To the study of ecological and zoogeographic structure of rove beetle (Staphylinidae, Coleoptera) assemblages of the beech forests of the northeast macroslope of the Ukrainian Carpathians - Lutska, M. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The structure of ecological and zoogeographic groups of rove beetles, which inhabit the beech forests of the Lower Forest Belt of the Northeastern macro-slope of the Ukrainian Carpathians, was studied. A total of 616 specimens of Staphylinidae, which belong to 55 species in 12 subfamilies, were recorded from the investigated area. The Staphylininae subfamily is characterized by the largest individual number (396) and the highest species richness (19). The dominant Staphylinidae species were Ocypus bicharicus (68 individuals, 11.2%), Ocypus olens (63 individuals, 10.4%), Staphylinus erythropterus (35 individuals, 5.8%), Staphylinus caesereus (35 individuals. 5.8%), Nudobius lenthus (33 individuals, 5.4%). The study of ecological and morphological adaptations of rove beetles to the habitats showed that the recorded species are representatives of 13 ecological/morphological groups in three classes. The highest species richness was typical to the representatives of the epibionts class (47.3% of the total species registered). A smaller number of species belonged to borers (36.3%). However, it should be noted that this class included the largest number of ecological/morphological groups of rove beetles (8 groups). The highest individual abundance within the given class was typical to the groups of running borers coprobionts and burrowing borers micetobionts that in total covered 14.6%. The class of cryptobionts makes up 16.3% of all identified species. Running subbark cryptobionts were the most numerous group within the given class (10.9%). By trophic specialization, most recorded species were predators (74.6%). A minor part of species belonged to myxophages, which combine zoophagia with miceto- or saprophagia. Together they made up 16.4% of the species found. Only two species belonged to micetophages and three species to nematophages. Analysis of geographic ranges has shown the prevalence of species with European and Holarctic distribution.